Phenoxy Radical Reactivity of Nucleic Acids: Practical Implications for Biotinylation. (27th January 2021) - Wilbanks, Brandon; Garcia, Brian; Byrne, Shane; Dedon, Peter; Maher, L. James
Abstract: Recent advances in peroxidase‐mediated biotin tyramide (BT) signal amplification technology have resulted in high‐resolution and subcellular compartment‐specific mapping of protein and RNA localization. Horseradish peroxidase (HRP) in the presence of H2 O2 is known to activate phenolic compounds for phenoxy radical reaction with nucleic acids, where biotinylation by BT is a practical example. BT reactivity with RNA and DNA is not understood in detail. We report that BT phenoxy radicals react in a sequence‐independent manner with guanosine bases in RNA. In contrast, DNA reactivity with BT cannot be detected by our methods under the same conditions. Remarkably, we show that fluorescein conjugates DNA rapidly and selectively reacts with BT phenoxy radicals, allowing convenient and practical biotinylation of DNA on fluorescein with retention of fluorescence. Abstract : Enzyme‐catalyzed phenoxy radical biotinylation, an increasingly important tool in biotechnology and molecular biology applications, is here shown to label guanosine bases in RNA, but not in DNA, under defined conditions. Remarkably, common fluorescein conjugates of synthetic DNA oligonucleotides are found to undergo facile biotinylation on fluorescein with retention of fluorescence. This convenient observation points to a variety of practical applications of peroxidase‐catalyzed chemistry for analysis of DNA conjugates in vitro and in cells.